High-Power and High-Reliability RF MEMS Switch Review - Tian, Wenchao; Hu, Jianglei (Recent Patents on Mechanical Engineering, 2014)
RF MEMS switch is one of new microwave devices with MEMS technology. Development directions of RF switch are high-power and high-reliability. It has many advantages, such as low loss, low power, excellent linearity, small size and easy integration. Its research status and performances are introduced in this paper. Relevant researches and patents are studied. Some measures to improve power and reliability are proposed. The application areas and major problems are analyzed. The development trends are presented.
Keywords: technology